1983
DOI: 10.3382/ps.0621786
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Ochratoxin A and Tannic Acid to Growing Chicks

Abstract: The effects of ochratoxin A (OA) and tannic acid (TA) on growing chicks were determined. One-day-old male broiler chicks were fed a diet containing the following additives for 26 days: A) none; B) 3.0 ppm OA; C) 1.5% TA; D) 3.0 ppm OA plus 1.5% TA. When compared to the controls, body weights and feed efficiencies were significantly depressed in the OA and TA groups. There was a further depression in body weights and a dramatic depression of feed efficiency in the OA-TA combination group. Pigmentation, as measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
2

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 19 publications
3
13
2
Order By: Relevance
“…Our results are consistent with this finding and support the reports of Huff et al (1974Huff et al ( , 1975, Prior et al (1980), Huff and Doerr (1981), and Kubena et al (1983) who observed that chicks fed diets containing OA had reduced performance. The depression in body weights due to V agrees with the earlier reports of Romoser et al (1961), Nelson et al (1962); Berg (1963), Hathcock et al (1964), and Kubena and Cysewski (1979).…”
Section: Resultssupporting
confidence: 96%
See 1 more Smart Citation
“…Our results are consistent with this finding and support the reports of Huff et al (1974Huff et al ( , 1975, Prior et al (1980), Huff and Doerr (1981), and Kubena et al (1983) who observed that chicks fed diets containing OA had reduced performance. The depression in body weights due to V agrees with the earlier reports of Romoser et al (1961), Nelson et al (1962); Berg (1963), Hathcock et al (1964), and Kubena and Cysewski (1979).…”
Section: Resultssupporting
confidence: 96%
“…The widespread occurrence of ochratoxin-producing fungi, their ability to grow on a variety of feedstuffs (Chu, 1974), and the natural occurrence of OA in corn (Shotwell et al, 1969), barley (Fischback and Rodericks, 1973), wheat (Scott et al, 1970;Prior, 1976), oats (Krogh, 1973), mixed feeds, dried white beans, and peanuts (Scott et al, 1972) combine to present a potentially great hazard to poultry. Experimental feeding of graded levels of OA in diets has been demonstrated to have a deleterious effect on growing chicks (Huff et al, 1974(Huff et al, , 1975Prior et al, 1980;Huff and Doerr, 1981;Kubena et al, 1983). dium, as the calcium salt, retarded the growth of chicks.…”
Section: Introductionmentioning
confidence: 97%
“…can cause liver and kidney disorders in rabbits and rats (Arheleger et al 1965, Boler et al 1966, Ca.mp et al 1967). Dietary tannin also has been shown to reduce growth rates in chickens (Vohra et al 1965, Fuller et al 1967, Conner et al 1969, Armstrong et al 1974, Kubena et al 1983). Quercetin (a flavonoid) and tannic acid (a hydrolyzable tannin).…”
Section: Low Population Densities Of Ruffed Grouse In Thementioning
confidence: 99%
“…The biochemical effects of ochratoxin in poultry include the decrease in serum total protein concentration, as a major clinical observation. Many authors (Bailey et al, 1990;Kubena et al, 1981;Kubena et al, 1985a) have described the negative effect of higher dietary OTA level (2.5-4.0 mg/kg) on broiler protein status, protein fraction and A/G ratio in the blood serum of broilers. On the other hand, there is limited data about the effect of dietary OTA levels below 2 mg/kg or less that are most frequently detected in feedstuffs (Nedeljkovi} Trailovi} et al, 2000).…”
Section: Introductionmentioning
confidence: 97%